Penomena Penggunaan Gadget Terhadap Minat Belajar Anak Usia Dini 5-6 Tahun Di TK Teratai Merah Kab. Bandung - Ageng Saepudin Kanda S; Didah Nurhidayah (Pusat Riset dan Inovasi Nasional, 2024)
Education is the key to the development of a nation. Education is carried out through efforts to determine all the natural strengths that children have, both as humans and as members of society, to achieve the highest safety and happiness. In line with this, the educational process should also be focused on the process of developing all human potential so that we can become ourselves with superior abilities and personalities so that we can create adequate resources. The method used in writing this article is a qualitative method. Qualitative research is research that looks at the perspective of social reality, namely by seeing the world as it is, therefore a qualitative researcher must be someone with an open mind. Basically, qualitative research has two objectives, namely: first, describing and revealing and second, describing and explaining. According to Ma'Tuf in M.Hatis, a gadget is a small technological electronic device or item that has a special function, but is often associated as an innovation or new item. A gadget among the public is no longer foreign, in this advanced era it is very sophisticated because the gadgets that are made are small and have many benefits and there are positive and negative sides to the use of gadgets. The use of gadgets in young children aged 5-6 years is indeed the use of gadgets It has a big influence on children because nowadays children are more concerned with playing with gadgets than studying and some of these children's families give their children a personal gadget.